Proximal factors influencing the likelihood of married and cohabiting women in Sierra Leone to use contraceptives. A cross-sectional study - Augustus Osborne; Camilla Bangura (BMC, 2024)
Abstract Background In the tapestry of reproductive health in Sierra Leone, where maternal mortality remains a poignant thread, understanding contraceptive use intentions among married and cohabiting women emerges as a vital motive. This study examines the intention to use contraceptives among married and cohabiting women in Sierra Leone. Methods The study analysed the 2019 Sierra Leone Demographic and Health Survey data. A total of 7846 married and cohabiting women comprised the study. A multivariable binary regression analysis was used to examine the predictors of intention to use contraceptives. The regression results were presented using an adjusted odds ratio (AOR) with 95% confidence intervals (CI). Results The proportion of intention to use contraceptives among married and cohabiting women was 47% in Sierra Leone. Married and cohabiting women living in the eastern region (AOR = 1.65, 95% CI = 1.18, 2.30), southern region (AOR = 1.45, 95% CI = 1.04, 2.01), secondary education (AOR = 1.42, 95% CI = 1.00, 2.01), listen to the radio at least once a week (AOR = 1.30, 95% CI = 1.08, 1.55), and four or more births (AOR = 2.97, 95% CI = 2.23, 3.96) had higher odds of being associated with intention to use contraceptives. The propensity to utilise contraceptives among married and cohabiting women in Sierra Leone declined as their age increased, especially women aged 45-49 (AOR = 0.07, 95% CI = 0.04, 0.11) who had the least intention of using contraceptives. Married women (AOR = 0.53, 95% CI = 0.39, 0.72) and women who read magazines or newspapers at least once a week(AOR = 0.61, 95% CI = 0.36, 1.o4) had lower odds of contraceptive use intention. Conclusion The findings of this study indicate that there is a moderate yet encouraging intention to use contraception among married and cohabiting women in Sierra Leone. Factors like residing in the eastern and southern regions, having secondary education, having more children and regular radio listening are associated with higher contraceptive use intentions. Older women, especially those nearing the end of their childbearing years, have the lowest intention. Married women and regular magazine or newspaper readers were less likely to intend to use contraceptives. These findings call for targeted interventions focusing on rural areas, women with lower education, and older women.